Framed: women in the family court underworld - Cocchiola, Christine M. (Narc Free Press, 2024)
This could be you-or your sister, mother, child, or friend. These stories are five-alarm warnings from real women around the world. Just like you perhaps, they had no idea what happens in the gender biased family court underword-until they found themselves in a divorce or custody fight. Dr. Christine Cocchiola and Amy Polacko are both survivors of domestic abuse who work with family court victims daily. This expose not only validates the experience of millions of women-but also warns about what mothers are up against in these battles, the harms inflicted on children, red flags to watch for while dating, and ways to protect yourself during marriage. If you are female, you can't afford not to read this book